Understanding Academic Grit: A Philosophical Study of Existence, Truth, and Values in Education - Riza Melinda; Wiryo Nuryono (International Journal Labs, 2026)
Academic grit has become an important construct in education as students increasingly face academic pressure, learning loss, motivational decline, and difficulties in maintaining perseverance toward long-term educational goals. However, most previous studies have examined grit through quantitative measurement, while its deeper philosophical meaning remains insufficiently explored. This study aims to analyze academic grit from the perspectives of ontology, epistemology, and axiology in order to understand its existence, the construction of its truth, and its value orientation in education. A qualitative Systematic Literature Review approach was employed using the PRISMA 2020 framework. Data were collected from relevant publications indexed in Scopus, Google Scholar, Garuda, and SINTA, focusing on studies published between 2020 and 2025 concerning academic grit, education, philosophy, qualitative inquiry, and collectivist culture. The data were analyzed using reflexive thematic analysis. The findings show that academic grit is not merely a psychological trait, but a mode of being reflected in students' perseverance during academic challenges. Epistemologically, grit is constructed through experience, failure, reflection, and social interaction. Axiologically, grit embodies values such as responsibility, purpose, patience, and commitment. This study concludes that academic grit should be understood as a philosophical, cultural, and educational phenomenon.